'Black Lives Have Always Mattered': Cultural specificity and transformative representations in Small Axe. (June 2023) - Dunleavy, Trisha
Small Axe, a series of five films, has brought innovation and prestige to TV drama not only for its overdue history of Caribbean migrant experiences in post-war Britain but also for its transformative representations of Black British people. The article examines three areas of the Small Axe production and text in recognition of their importance to these achievements: its creative genesis as a TV drama inspired by the under-representation of Britain's Caribbean diaspora; the opportunities it gained as a BBC commission and Amazon coproduction; and the indicators and outcomes of its deployment of the four 'markers' of Third Cinema textuality.